Parents' Oral and Dental Health Behavior as Predictors of Children's Oral and Dental Health Status - Dayu Annesti Viana; Sri Pandu Utami (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2022)
Background: Knowledge Parents are considered to have the to teach their children basic things about maintaining a healthy body. The implantation of oral health behavior should start at an early age and start from the family environment. Childhood is the beginning of behavior formation, therefore parents are expected to be able to educate their children to behave properly to maintain healthy teeth and mouth. Objective: The purpose of this study was to determine the oral health behavior of parents to determine the oral health status of children in the pedodontics department of the Baiturrahmah University Dental Hospital. Methods: This research type is quantitative with analytic survey method with cross sectional research design. The population was pediatric patients who took care at the Paedodonti Department of the Baiturrahmah Hospital in July 2020. Result: The results showed that the educational status, tooth brushing behavior, eating sweet eating behavior, the habit of bringing children to the dentist and complaints in the oral cavity of the parents gave a picture. Predictions for their children about oral health. Conclusion: Parents' behavior will have an effect on their children because indirectly the habits of parents will be imitated and made an example for their children.